Commercialisation strategies of technology-based European SMEs: Market for technology vs. markets for products - Paola Giuri; Alessandra Luzzi (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2005)
This paper focuses on European small- medium serial innovators at the beginning of the 1990s and provides an empirical basis to answer the following questions: who are the upstream specialized small- medium technology producers? How are they distributed across countries? Are there technologies in which they show a relative advantage? By focusing on firms' history, activities, and the description of events obtained by different data sources, we also investigates if technology based SMEs choose to implement a strategy based on the commercialisation of their technologies or if they invest in the complementary assets of production, marketing and distribution becoming micro-chandlerian firms. Through this analysis we are able to propose a taxonomy of technology based SMEs' strategies in the market for technology, in the market for embedded technologies and in the market for products.
Keywords: 330; SMEs; Technology Strategies; Licensing; Innovationsmanagement; KMU; EU-Staaten